CompTIA security+ study guide - Dulaney, Emmett A. (Wiley Pub., 2011)
"The preparation you need for the CompTIA Security+ exam SY0-301This top-selling study guide helps candidates prepare for exam SY0-301 and certification as a CompTIA Security+ administrator. Inside the new edition, you'll find complete coverage of all Security+ exam objectives, loads of real-world examples, and a CD packed with cutting-edge exam prep tools. The book covers key exam topics such as general security concepts, infrastructure security, the basics of cryptography, and much more. Provides 100% coverage of all exam objectives for the CompTIA Security+ exam SY0-301 Covers key topics such as general security concepts, communication and infrastructure security, the basics of cryptography, operational security, and more Offers practical examples and insights drawn from the real world Includes a CD with two practice exams, all chapter review questions, electronic flashcards, and more Obtain your Security+ certification and jump-start your career. It's possible with the kind of thorough preparation you'll receive from CompTIA Security+ Study Guide, 5th Edition"--
Print version record
Keywords: Electronic data processing personnel -- Certification; Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures; Examinations; Computer security; Examinations; Electronic data processing personnel; Certification; Study guides